2021
DOI: 10.3389/fpsyg.2021.675285
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a Useful Intervention to Reduce Alcohol Consumption and Improve Physical Fitness in Individuals With Alcohol Use Disorder: A Systematic Review and Meta-Analysis

Abstract: Objective: This meta-analysis and systematic review examined the effects of exercise interventions on alcohol consumption and binge drinking in individuals with alcohol use disorder (AUD).Data sources: PubMed, Web of Science, Google Scholar, SPORTDiscus, and ERIC databases.Study Inclusion and Exclusion Criteria: Peer-reviewed randomized controlled trials published in English between 1970 and 2021. All studies compared exercise (Ex) and treatment as usual (TAU) to TAU in adults with an alcohol-related diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Interventions involving physical activity are also an accessible way of reducing the symptoms of severe anxiety or mental illness among adults, including schizophrenia-spectrum disorders, major depressive disorder, and bipolar disorder [ 14 18 ]. The effects of physical activity as an additional or stand-alone treatment are sustained in the case of other medical conditions such as: alcohol use disorder [ 19 23 ]; functional outcome after stroke [ 24 30 ]; cardiovascular disease [ 31 ]; type 2 diabetes [ 32 ]; cancer [ 33 ]. This double role of physical activity [ 34 ] reflects its negative association with demand of health services, which could lead to lower spending on healthcare systems [ 3 , 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions involving physical activity are also an accessible way of reducing the symptoms of severe anxiety or mental illness among adults, including schizophrenia-spectrum disorders, major depressive disorder, and bipolar disorder [ 14 18 ]. The effects of physical activity as an additional or stand-alone treatment are sustained in the case of other medical conditions such as: alcohol use disorder [ 19 23 ]; functional outcome after stroke [ 24 30 ]; cardiovascular disease [ 31 ]; type 2 diabetes [ 32 ]; cancer [ 33 ]. This double role of physical activity [ 34 ] reflects its negative association with demand of health services, which could lead to lower spending on healthcare systems [ 3 , 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“… 31 32 It is also likely that football players are more physically active than the general population. Physical exercise is hypothesised to reduce alcohol consumption and has been suggested as a treatment for alcohol related disorders, 33 although some studies show an association between higher physical activity levels and risk of certain alcohol related disorders. 34 35 We also found that the elite football players had higher income than men from the general population, which could potentially protect against misuse of alcohol and other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is planned, structured, repetitive, and intentional physical activity intended to improve or maintain physical tness (8). Exercise has been suggested as an adjunctive treatment strategy for people with substance use disorder (7) due to its positive effects on health, quality of life and reducing the burden of substance use disorder patterns (9,10). Physical activity and exercise can be effective adjunctive treatment methods for reducing nicotine, alcohol and drug use (7,11,12).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%